ERGONOMIC INTERVENTION IN ORGANIZATION AND WORK STATION INCREASES STUDENT’S WORK PERFORMANCE AND EFFICIENCY OF ELECTRICAL ENERGY CONSUMPTION - Sudiajeng, Lilik; Adiputra, N.; Manuaba, A.; Sutjana, D.P. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Woodworking workshop could be hazardous to workers’ health, particularly when itis done improperly. Workers could be exposed to the following risks such as overexertion,repetitive motion, noise, dust, and chemicals that may threaten workers’ health; decreaseswork inefficiency and excessive strains due to inappropriate working condition or posture.This study was conducted to examine the effect of ergonomics intervention in the students’work performance and the efficiency of the electrical energy consumption at thewoodworking workshop of Bali State Polytechnic.This is an experimental study with pre and post test control group design. Subjectswere divided into 4 groups of students, each consisting of 10 students, all performing thesame task with different working condition: (1) the original working condition for controlgroup (CG); (2) a new organization for treatment group 1 (TG1); (3) a new work station fortreatment group 2 (TG2); and (4) both new organization and work station for treatmentgroup 3 (TG3). Normally distributed and equal data were analyzed by using the One WayAnova test and followed by the Post Hoc–LSD test, and the remaining data were analyzedby using the Kruskal Wallis test and followed by the Mann-Whitney test at the level ofsignificance ? = 0.05.Result showed that students’ work performance in TG1 increased in moderately,while those in TG2 and TG3 increased very considerably. Moreover, there was nosignificant increased of the efficiency of electrical energy consumption in TG1 (p > 0.05),but there were significant increased of electrical energy consumption of about 44.74% and107.89% respectively in TG2 and TG3 (p < 0.05). This gain were accompanied by savingcost of the electrical energy consumption of about 38.64% and 58.68% respectively. It alsoappeared that the increased students’ work performance and the efficiency of electricalenergy consumption were highest in TG3.In conclussion, it may be stated that comprehensive ergonomic intervention in boththe organization and work station in an effort to apply total ergonomic approach hasproduced the best effect in terms of increased students’ work performance and efficiency ofelectrical energy consumption at the woodworking workshop Bali State Polytechnic.
Keywords: ergonomics intervention, organization, work station, work performance, electrical energy consumption